Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Gojek: The Effect of Promotion and Service Quality on Customer Satisfaction at Gojek - Anggi Maulidya; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2026)
The development of this increasingly advanced era, encourages many things to develop and innovate, including in the field of transportation. Promotion activities and attention to Service Quality carried out by the Gojek company can be a way for the company to continue to survive and continue to compete with other online transportation companies. The purpose of this study is to determine the effect of promotion and service quality on customer satisfaction on Gojek users. The research method used in the study is a quantitative research method with hypothesis testing. In data collection, the method used is the questionnaire method. Determination of the number of samples in this study was taken using a purposive sampling technique, and using 50 Gojek user respondents in the Jakarta area. The data analysis method uses multiple regression tests. The research that has been conducted shows that the promotion and service quality variables have a positive and significant influence on the Customer Satisfaction variable. The results are shown by the results of the promotion t-test, the results of which are shown by a significance value of 0.005 which is smaller than 0.05 and a calculated t value of 2.949 which is greater than the t table of 2.013. The results of the service quality t-test are also proven to have a significant effect on customer satisfaction (Y), with a significance value of 0.001 (<0.05) and a calculated t of 6.292 (> 2.013). And from the results of the f-test, it is shown by a significance value of 0.000 which is smaller than 0.05 and a calculated F value of 206,510 which exceeds the F table of 3.20. Which shows that there is an influence between Promotion and Service Quality on Customer Satisfaction